2009
DOI: 10.1159/000213494
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Advantages in Recent Central Dialysis Fluid Delivery System

Abstract: The central dialysis fluid delivery system (CDDS) has been working exclusively in Japan since 1970, a fact which proves that CDDS is useful in the multi-patient treatment with in-center regular hemodialysis. It is a cost-effective, labor-saving and time-tested system with 40 years of experience. Microbial safety is improved by a refined system design, multiple endotoxin retentive filters (ETRF) and daily overnight disinfection of the entire system. Consequently, the usage of backfiltered dialysate is now accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Accordingly, it has been suggested that DCa be individualized by CKD‐MBD status in each patient . However, in Japan, where a central dialysate fluid delivery system is common , it is more difficult to use individualized DCa baths. The results presented here show the effects of conversion of DCa from 3.0 to 2.75 mEq/L on mass dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been suggested that DCa be individualized by CKD‐MBD status in each patient . However, in Japan, where a central dialysate fluid delivery system is common , it is more difficult to use individualized DCa baths. The results presented here show the effects of conversion of DCa from 3.0 to 2.75 mEq/L on mass dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ability to supply a large amount of dialysis fluid is only temporary in CDDS, it is possible to use many patient monitors [12,13].…”
Section: Dialysis Fluid Delivery Systemsmentioning
confidence: 99%
“…Standard reverse osmosis discharges more water than it actually produces for dialysis; the recovery ratio, i.e. the percentage of depurated water used for dialysis, can be over 80%, if the newer systems are employed; these are more expensive and the lifespan of the reverse osmosis membranes is often considerably shorter, especially when reverse osmosis is not coupled with a water softener system [9,19,27,31,[52][53][54][55][56][57].…”
mentioning
confidence: 99%
“…Centralised water preparation systems, available since the late 1970s, and particularly diffused in Japan, are The circular "cradle to cradle" model: technical waste should nourish the technical cycle, similar to organic waste, nourishing plants and being continously recycled in the biosphere increasingly being used: they combine water treatment with dialysis fluid preparation, both for haemodialysis and for haemodiafiltration [53][54][55][56][57]. This partly compensates for the higher costs of HDF and the avoidance of plastic bags for reinfusion is of obvious interest not only for reducing waste, but also as for water consumption.…”
mentioning
confidence: 99%